Respuestas

2012-04-13T00:35:20+02:00

12 + {13 - [(9 - x) +10] - 4} = 9

12 + [13  - (9 - x + 10) ] - 4 = 9

12 + (13 - 9 + x - 10) - 4 = 9

12 + 13 - 9 + x - 10 - 4 = 9

x = 9 - 12 - 13 + 9 + 10 + 4

x = 7

 

Suerte! :)

2012-04-13T00:50:44+02:00

BUENAS TARDES.12+{13+[(9-X)+10]-4}=9

                          12+{13-[+9-X+10]-4=9
                          12+{13-9+X-10-4}=9
                          12+13-9+X-10-4=9
                           X=9-12-13+9+10+4
                           X=-25+32
                           X=7
12+13-9+7-10-4=9
32-23=9
9=9          SALUDOS.